Managing IT in a Downturn. - Mitchell, Stewart (IT Governance Pub., 2008)
Against this backdrop of turbulence, this pocket guide examines what IT executives can do to stretch budget to maintain a useful and reliable network of IT services, and examine where new technologies, free software and licence renegotiation can make budgets work harder. Because all companies are different, the intention is not to recommend specific changes, but to raise the questions and possibilities that will provoke improvements.
Keywords: Electronic data processing departments -- Management.; Information technology -- Economic aspects.; Information resources management -- Economic aspects.; Information technology -- Planning.; Data processing service centers -- Management.; Centres de traitement de l'information -- Gestion.; Technologie de l'information -- Aspect économique.; Gestion de l'information -- Aspect économique.; Technologie de l'information -- Planification.; COMPUTERS -- Computer Literacy.; COMPUTERS -- Computer Science.; COMPUTERS -- Data Processing.; COMPUTERS -- Hardware -- General.; COMPUTERS -- Information Technology.; COMPUTERS -- Machine Theory.; COMPUTERS -- Reference.; COMPUTERS -- General.; Electronic data processing departments -- Management; Information technology -- Economic aspects; Information technology -- Planning